Implementation of an Executive Information System for Thesis Document Submission with the Addition of AES-256-CBC Cryptography Algorithm - Aufa, Taqiyuddin Ahmad Al; Rivaldy, Adriano Femaz; Arifiyanti, Amalia Anjani; Putra, Agung Brastama (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The rapid digitalization of higher education demands secure and efficient management of academic documents such as thesis submissions. This study aims to develop an Executive Information System (EIS) for Thesis Document Submission integrated with AES-256-CBC cryptographic security to ensure data confidentiality, integrity, and controlled access. The system is implemented as a web-based platform using the Laravel framework and MySQL database, where each uploaded thesis document is automatically encrypted, and only authorized users with a valid Master Key can decrypt it. The AES-256-CBC algorithm generates unique ciphertexts for every encryption process, supported by randomized Initialization Vectors and separate key management to prevent unauthorized access or data leakage. Furthermore, the EIS dashboard implements the drill-down method, presenting real-time analytical information. This allows academic leaders to navigate hierarchically from high-level summaries to specific, detailed data, enhancing their ability to monitor thesis submissions and make informed decisions effectively. The results indicate that the integration of cryptography and executive information management enhances both document security and administrative efficiency, providing a reliable and transparent solution for safeguarding academic data within higher education institutions.